Ensaio de motor ciclo diesel com diferentes proporções de biodiesel de algodão - Laurindo, Geovani Marques (2018)
Cotton is the main fibrous plant in the world, and many studies are needed to add more value to cottonseed, which is a source of protein and oil with high potential for the production of biofuels. The objective of this work was to evaluate the performance of a diesel cycle engine and its emissions when using commercial diesel S10 and mixtures with biodiesel of cotton oil. It was analyzed pure S10 and blends B2, B6, B12, B20, B24, B50, B80 and B100, considering that commercial diesel S10 already has 8% biodiesel in its composition. An A950 Tractor was used for the tests. In order to perform the tractor performance tests, the methodology indicated in the ABNT NBR ISO 1585 standard was used and for the emissions tests the standard NBR 14489. The obtained results were similar to several researches, in which there were a decrease in torque and power of the engine with the use of 100% biodiesel. The mixtures with commercial diesel tended to be higher in torque and power with the use of 100% commercial diesel. Regarding emissions, there was a decrease in hydrocarbon emissions with the addition of biodiesel from cotton oil in commercial diesel, while monoxide and carbon dioxide levels increased with the increase of biodiesel proportion in diesel. It can be concluded that the most technically feasible mixture in this work was B24, which presented higher values of torque and power, with medium consumption between the blends.